Quantification of upper limb kinetic asymmetries in front crawl swimming - Morouço, Pedro (2020)
This study aimed at quantifying upper limb kinetic asymmetries in maximal front crawl swimming and to examine if these asymmetries would affect the contribution of force exertion to swimming performance. Eighteen high level male swimmers with unilateral breathing patterns and sprint or middle distance specialists, volunteered as participants. A load-cell was used to quantify the forces exerted in water by completing a 30s maximal front crawl tethered swimming test and a maximal 50 m free swimming was considered as a performance criterion. Individual force-time curves were obtained to calculate the mean and maximum forces per cycle, for each upper limb. Following, symmetry index was estimated and breathing laterality identified by questionnaire. Lastly, the pattern of asymmetries along the test was estimated for each upper limb using linear regression of peak forces per cycle. Asymmetrical force exertion was observed in the majority of the swimmers (66.7%), with a total correspondence of breathing laterality opposite to the side of the force asymmetry. Forces exerted by the dominant upper limb presented a higher decrease than from the non-dominant. Very strong associations were found between exerted forces and swimming performance, when controlling the isolated effect of symmetry index. Results point that force asymmetries occur in the majority of the swimmers, and that these asymmetries are most evident in the first cycles of a maximum bout. Symmetry index stood up as an influencing factor on the contribution of tethered forces over swimming performance. Thus, to some extent, a certain degree of asymmetry is not critical for short swimming performance.